Recycling from SI+SA exhibition in the context of visual arts / Hairulnisak Merman … [et al.] - Merman, Hairulnisak; Zakaria, Muhammad Salehuddin; Ismail, Issarezal; Amir Hamzah, Ahmad Fauzi (Faculty of Art and Design, 2021)
This study was conducted to discuss and identify the potential of discarded recycled materials from the daily use of society in Malaysia and turns them to produce creative artworks. The study was conducted based on the observations of the artworks exhibited during the SI+SA Exhibition at the Shah Alam Gallery, Selangor. This research focuses on the creation process, form and value of the creative artworks originating from recycled materials. The art study approach, where the foundations are derived from a qualitative approach that emphasizes descriptive and holistic explanatory systems, has been used and linked through a conceptual framework developed by the relevant concepts as the frame of its analysis. Data was collected through primary methods such as interviews and observations and secondary sources such as books, journals, newspaper clippings and magazines. The results show that the works from the SI+SA Exhibition attempted to convey a message to address humanitarian problems such as responsibility, behaviour, awareness and sacrifice. The structure of the message conveys content that represents the meaning of the values of health, hygiene and creativity that ultimately encourages the community to play their respective roles in addressing the issue of waste management and recycling on a global scale. It is hoped that this research can show that using recycled materials as an alternative to producing creative artwork is a practical approach. Indirectly, raising awareness about recycling is no longer an option but rather an obligation to all levels of society to be cultured in daily life to ensure the environment's future is secure.